Effects of Alcohol and Cocaine in a Mutant Mouse Model of Predisposition to Post-Traumatic Stress Disorder - Eleni Paizanis; Michela Crotti; Anthony Petit; Mathilde Règue; Virginie Beray-Berthat; Florence Noble; Laurence Lanfumey; Raymond Mongeau (Frontiers Media S.A., 2020)
Comorbidity between drug abuse and post-traumatic stress disorder (PTSD), a stress-related dysregulation of fear responses, is very high. While some drugs are known to increase fear and anxiety, there are only few data regarding interactions between voluntary drug consumption and fear memory. The spontaneous chronic consumption of either alcohol or cocaine under a 3-week free-choice progressive paradigm of alcohol (3/6/10%) or cocaine (0.2/0.4/0.6 mg/ml), was assessed in VGV transgenic mice, having full 5-HT2C receptor editing and displaying PTSD-like behaviors. The consequences of these drug consumptions on the potentiated contextual and cued fear conditioning responses of VGV mice were assessed. The effects of drugs on hippocampal brain-derived neurotrophic factor (Bdnf) mRNA were measured as its expression was previously found to be decreased in VGV mice. Chronic alcohol consumption was similar in WT and VGV mice. In the alcohol condition, fear acquisition was not different at the end of the learning session and cue-fear extinction was facilitated. Regarding cocaine, in contrast to WT mice, VGV mice did not increase their drug consumption along with increasing doses, an effect that might be related with enhanced drug stimuli discrimination via increased 5-HT2C receptors. Cocaine-intake VGV mice did not display the contextual fear generalization usually observed in control VGV mice. In addition, Bdnf expression was upregulated after either chronic alcohol or cocaine intake. Altogether, these results suggest that both chronic alcohol and cocaine voluntary oral consumptions can exert some therapeutic-like effects in a mutant model of PTSD predisposition.